2012
DOI: 10.4103/0019-5049.98767
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dexmedetomidine and clonidine (α2 agonist drugs) as an adjuvant to local anaesthesia in supraclavicular brachial plexus block: A randomised double-blind prospective study

Abstract: Background and Objectives:Alpha-2 agonists are mixed with local anaesthetic agents to extend the duration of spinal, extradural and peripheral nerve blocks. We compared clonidine and dexmedetomidine as an adjuvant to local anaesthetic agent in supraclavicular brachial plexus block with respect to onset and duration of sensory and motor block and duration of analgesia.Methods:Sixty ASA I and II patients scheduled for elective upper limb surgeries under supraclavicular brachial plexus block were divided into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
199
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(231 citation statements)
references
References 18 publications
29
199
2
1
Order By: Relevance
“…8 Swami et al concluded that dexmedetomidine (1μg/kg) when added to local anaesthetic (bupivacaine 0.25%) in SBPB increased the duration of sensory and motor block and also the duration of analgesia. 3 Similar prolongation of duration of block was also observed by Esmaoglu et al in their study to evaluate the effect of dexmedetomidine (100µg) as additive to levobupivacaine (40ml of 0.5% levobupivacaine) in axillary brachial plexus block. 9 Zhang et al also recorded prolonged sensory and motor blockade duration in patients who received 50μg dexmedetomidine in 40ml of 0.33% ropivacaine when compared to control group for axillary brachial plexus blockade.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…8 Swami et al concluded that dexmedetomidine (1μg/kg) when added to local anaesthetic (bupivacaine 0.25%) in SBPB increased the duration of sensory and motor block and also the duration of analgesia. 3 Similar prolongation of duration of block was also observed by Esmaoglu et al in their study to evaluate the effect of dexmedetomidine (100µg) as additive to levobupivacaine (40ml of 0.5% levobupivacaine) in axillary brachial plexus block. 9 Zhang et al also recorded prolonged sensory and motor blockade duration in patients who received 50μg dexmedetomidine in 40ml of 0.33% ropivacaine when compared to control group for axillary brachial plexus blockade.…”
Section: Discussionsupporting
confidence: 58%
“…Motor block was graded using modified Bromage scale for upper extremities. 3 Grade 0: Normal motor function. Grade 1: Ability to move only fingers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 One negative aspect that hinders the single-shot technique is the limited duration of action of the local anesthetic. Although several studies have described prolonging the block with adjuvants, such as dexmedetomidine, clonidine, and epinephrine, 6,7 limited data exist on the safety profile of placing these adjuvants adjacent to the neural tissues. Consequently, patients who have been discharged after undergoing a single-shot supraclavicular block during a procedure may experience postoperative pain shortly after arriving home from the hospital, or even in transit.…”
Section: Résumémentioning
confidence: 99%
“…Based on other reported data 7 and our clinical experience, we estimated the duration (SD) of analgesia to be 300 (60) min after a single-shot supraclavicular block. We expected the second bolus of local anesthetic given through the catheter in the PARR to have a similar duration of action and assumed it would prolong the duration of analgesia by at least 90 min compared with the control group.…”
Section: Sample Size Calculationmentioning
confidence: 99%